Meningkatkan Hasil Belajar Siswa Pada Operasi Perkalian dan Pembagian Melalui Pendekatan Kontekstual di Kelas III UPT SD Negeri 179 Tamasongo Kabupaten Jeneponto - Dwi Fidar Ningsih; Haerul Syam; Hamdana Hadaming (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
The main problem in this study was the low learning outcomes of students in grade III SDN 179 Tamasongo, Jeneponto Regency on multiplication and division operations. This study aims to improve student learning outcomes in multiplication and division calculation operations in grade III students of UPT SD Negri NO 179 Tamasongo, Bontoramba District, Jeneponto Regency. This research is a Class Action Research (PTK). The location of this research was carried out at UPT SD Negri NO 179 Tamasongo, Bontoramba District, Jeneponto Regency. The subjects in this study were grade III students of SDN 179 Tamasongo, Jeneponto Regency with a total of 11 students consisting of 4 male students and 7 female students. The collected data is then analyzed using quantitative analysis. Quantitative data analysis is used to view student learning test result data. The results achieved in this study are: (1) There is an increase in student learning activities and teacher activities in each cycle. (2) In the first cycle, the average value of learning outcomes of grade III students of SDN 179 Tamasongo, Jeneponto Regency, was 56.3, while in the second cycle, the average value of learning outcomes was higher which reached 77. The completeness of learning mathematics on the material of multiplication operations and division of grade III students of SDN 179 Tamasongo, Jeneponto Regency has also improved. In cycle I, out of 5 (45%) students achieved learning completeness, while in cycle II as many as 11 (100%) students achieved learning completeness and classical learning completeness was achieved. This means that learning completeness in cycle II is achieved classically because the number of students who complete reaches 100%. Based on the results of the research mentioned above, it can be concluded that the learning outcomes of multiplication and division operations through a contextual approach (Contekxtual Teaching and Learning) in building space material in grade III SDN 179 Tamasongo Jeneponto Regency have increased.